Estructura y estado silvicultural de un rodal de capirona (Calycophyllum spruceanum) en un bosque aluvial de Belén, Iquitos, Perú.2022 - Davila Diaz, Ander (2024)
The study was carried out in a natural plantation of C. spruceanum located on the “Cuerito” farm, in the community of “Mohena Caño”, district of Belén, province of Maynas, Loreto. The objective of the study was to determine the structure and silviculture of the plantation that grows in flood-prone areas. The plantation reports a total of 277,6 trees/ha, total basal area of 12,8 m2/ha and commercial volume of 58.3 m3/ha. A total of 221 plants had partial upper light (38.43%), and 179 had emergent lighting (31.13%). The largest number of plants have a good crown shape with 348 plants (60.63%). A total of 491 plants have a very straight and cylindrical stem, without defects, which represent 85.39% of the total. Carry out selective thinning as a silvicultural treatment due to the diametric distribution of the plants in the stand in order to provide sufficient spacing to favor the growth of the stem in diameter and height and vigor of the crowns, as well as carry out different intensities of thinning, which allows comparison. the results of the treatment with the untreated stand.